Solve and check result: 5t - 3 = 3t - 5

Asked by Aaryan | 1 year ago |  107

##### Solution :-

5t - 3 = 3t - 5

On transposing 3t to L.H.S and -3 to R.H.S, we obtain

5t - 3t = -5 - (-3)

2t = -2

On dividing both sides by 2, we obtain

t = -1

L.H.S = 5t - 3 = 5 x (-1) - 3 = -8

R.H.S = 3t - 5 = 3 x (-1) - 5 = - 3 - 5 = -8 L.H.S. = R.H.S.

Hence, the result obtained above is correct.

Answered by Sakshi | 1 year ago

### Related Questions

#### Solve the inequations and graph their solutions on a number line  – 1 < (x / 2) + 1 ≤ 3, x ε l

Solve the inequations and graph their solutions on a number line  – 1 < ($$\dfrac{x}{2}$$) + 1 ≤ 3, x ε l

#### Solve the inequations and graph their solutions on a number line – 4 ≤ 4x < 14, x ε N

Solve the inequations and graph their solutions on a number line – 4 ≤ 4x < 14, x ε N

#### Solve (x / 3) + (1 / 4) < (x / 6) + (1 / 2), x ε W. Also represent its solution on the number line.

Solve ($$\dfrac{x}{3}$$) + ($$\dfrac{1}{4}$$) < ($$\dfrac{x}{6}$$) + ($$\dfrac{1}{2}$$), x ε W. Also represent its solution on the number line.

If the replacement set is {-3, -2, -1, 0, 1, 2, 3}, solve the inequation $$\dfrac {(3x – 1) }{2} < 2$$. Represent its solution on the number line.
Solve the inequations ($$\dfrac{3}{2}$$) – ($$\dfrac{x}{2}$$) > – 1, x ε N